Measurement of Additional Strains in Shaft Lining Using Differential Resistance Sensing Technology - Guangsi Zhao; HuaFu Pei; Hengchang Liang (International Journal of Distributed Sensor Networks)
As is well known, shaft lining fracture is the main disaster resulting in a large amount of fatalities and property loss. Thus, the additional strain is a key parameter to evaluate the safety condition of existing shaft linings. In this study, a new type of safety monitoring system based on differential resistance sensing technology is developed to measure the additional strain in shaft linings. In this paper, the theatrical study, the working principle, and the function of the newly developed monitoring system are fully presented. To investigate the reliability and effectiveness of the monitoring system, the differential resistance sensors are used to measure the horizontal and vertical strains at different elevations in a shaft lining during reinforcing the fracture inside the shaft lining. It can be found that from the test results the monitoring system based on differential resistance sensing technology can measure the deformation of the existing wall lining during stratum grouting. Therefore, it can be concluded that the newly developed monitoring system is significant for fracture warning and reinforcement engineering.